The relationship between bullying and self-worth in children with movement coordination problems - Piek, Jan; Barrett, Nicholas; Allen, Linsey; Jones, Anna; Louise, Marcelle (The British Psychological Society, 2005)
Background. Past research has indicated that there is a negative relationship between victimization and self-worth. Furthermore, children with movement problems such as developmental coordination disorder (DCD) are considered at risk of both victimization and low self-worth. Aims. This study investigated the relationship between peer-victimization and self-worth in a group of children with DCD and control children. Sample. Forty-three children aged 7–11 years were identified as at risk of DCD, and were matched on age and gender with 43 control children. Method. Children were individually assessed using the Multi-dimensional peer victimization scale (MPVS; Mynard & Joseph, 2000) to assess the degree and type of bullying, and the self perception profile for children (SPPC; Harter, 1985) to determine self-worth. Results. The two groups did not differ significantly on mean reported self-worth or mean peer-victimization. The relationship between these two measures, however, differed across group and gender. Peer victimization and self-worth were negatively correlated only for the children at risk of DCD. Furthermore, peer victimization accounted for a greater and statistically significant proportion of the variance in the self-worth of girls at risk of DCD compared with boys. This effect of peer-victimization on self-worth in girls with DCD was uniquely attributed to the effects of verbal victimization. Conclusions. Although children with and without motor coordination problems reported equivalent amounts of victimization, there were differences in the impact of that bullying. Specifically, self-worth was negatively affected by bullying for the girls with DCD. Teachers and parents should not only focus on the amount of bullying a child receives, but should also be aware of how bullying impacts differently on self-worth across groups.